Costs of Epilepsy in Austria: Unemployment as a primary driving factor. (July 2021) - Pirker, S.; Graef, A.; Gächter, M.; Baumgartner, C.
Highlights: This is the first detailed cost-of-epilepsy study in Austria. It confirms previous European findings for Austria, especially indirect costs as primary driver. High indirect costs underline the importance of the patient's ability to work. Abstract: Purpose: Epilepsy is one of the most common chronic neurological disorders, and long-term treatment with antiseizure medication is often central to its management. The costs of antiseizure medication are more evident than other disease-related costs; thus, we assessed the direct and indirect costs of epilepsy focusing on both drug expenditure and other cost-driving factors. Methods: Outpatient records and questionnaires applied in a tertiary epilepsy centre in Vienna were used in this bottom-up cost-of-illness study to evaluate disease duration, age at onset, epilepsy syndrome, seizure frequency, sex, healthcare utilisation, diagnostic evaluations, antiseizure medication, and occupation. Cost data were clustered in a histogram-based data analysis, and multivariate regressions were performed to identify cost drivers. Results: The average annual costs of 273 patients amounted to €9, 256 ($10, 459): €4, 486 ($5, 069) direct costs and €4, 770 ($5, 390) indirect costs. A histogram of semi-annual costs revealed distinct groups with low costs (< €2, 500 = $2, 825) and high costs (> €2, 500 = $2, 825). Seizure-free patients were clustered in the group with low costs; patients with ongoing seizures appeared more frequently in the group with high costs. Working patients were more often found in the group with low costs, whereas unemployed patients were more prevalent in the group with high costs. The regression analysis confirmed worklessness as the main cost driver. Conclusion: Non-productivity and poorly controlled disease with ongoing seizures are associated with higher costs in epilepsy. Providing high-level care and optimal drug treatment that enables patients to remain in work may help reduce the economic burden of epilepsy.